Antecedent Strategic Alignment and Its Effect on Business Resilience - Sabihaini, Sabihaini; Astuti, Sri; Perwira, Rifki Indra; Marita, Marita (Technium Social Sciences Journal, 2023)
The Covid-19 pandemic, which has been around for about 2 years, has impacted all sectors, especially the economic and industrial sectors. For SMEs, the Covid-19 pandemic is a challenge for cost and financial disruptions, activity disruptions, and existence difficulties. Many companies and SMEs have experienced bankruptcy and were unable to survive amid the Covid- 19 pandemic outbreak. Therefore, this research was established to propose antecedent strategic alignment that can build business resilience. In this study, the unit of analysis is SMEs in Sleman, Yogyakarta. The sample in this study was 94 SMEs. The analysis outcome of this study indicates that communication between business management and information technology management, strategic information system planning, information technology infrastructure flexibility, and environmental uncertainty have an effect and can become an antecedent of strategic alignment and in the end, strategic alignment has an effect on business resilience in a positive and significant way. The findings are interesting because it turns out that during the Covid-19 pandemic, strategic alignment can be a predictor of business resilience. Where business resilience has the nature of proactive anticipation before turbulence, adaptive when turbulence occurs, and reactive after turbulence occurs. And this is also the novelty of this research.